The Benefits of Self-Transcendence: Examining the Role of Values on Mental Health Among Adolescents Across Regions in China - Liu, Ping; Wang, Xiaofeng; Li, Dan; Zhang, Rongwei; Li, Hui; Han, Jingxin (Frontiers in Psychology, 2021)
As one of the foundations of existential positive psychology, self-transcendence can bring positive intrapersonal and interpersonal outcomes, especially in the COVID-19 era in which people are suffering huge mental stress. Based on Schwartz's theory of human basic values, the current study combines variable-centered and person-centered approaches to examine the relationships between adolescents' values and mental health across two regions in China. The results generally showed that (1) both self-enhancement and conservation values were positively correlated with depression and loneliness, while both self-transcendence and openness to change values negatively correlated with depression and loneliness. The results also showed that (2) there were four value clusters (i.e., self-focus, other-focus, anxiety-free, undifferentiated), and, compared to adolescents in the self-focus and undifferentiated values cluster, all adolescents in the anxiety-free values cluster reported lower depression and loneliness, while all adolescents in the other-focus values cluster reported higher depression and loneliness. The differences between the two regional groups only emerged in depression. Specifically, adolescents in Shanghai have higher levels of depression than adolescents in Qingdao. This study provides some evidence for the new science of self-transcendence among adolescents and also sheds light on how we may improve the level of mental health during the COVID-19 era.